2020
DOI: 10.1016/j.cell.2020.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Sulfolipid-1 Activates Nociceptive Neurons and Induces Cough

Abstract: publicly funded repositories, such as the WHO COVID database with rights for unrestricted research re-use and analyses in any form or by any means with acknowledgement of the original source. These permissions are granted for free by Elsevier for as long as the COVID-19 resource centre remains active. Article Mycobacterium tuberculosis Sulfolipid-1 Activates Nociceptive Neurons and Induces Cough Graphical Abstract Highlights d An Mtb organic extract activates nociceptive neurons and induces cough in guinea pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 103 publications
0
63
0
Order By: Relevance
“…Little work has been done to understand how viral infections and sensory neurons interact to promote or suppress the immune response. However, the existing literature on sensory innervation of the airway and lung with bacterial pathogens suggests that sensory afferents can have detrimental and beneficial effects depending on the context (Chiu et al, 2012;Chavan et al, 2018;Ruhl et al, 2020). We have interpreted our interactome findings under the assumption that neurogenic responses may worsen the disease state in COVID-19, potentially leading to ARDS Table 3 Differentially expressed genes in BALF of COVID-19 patients that are known to be regulated by MNK -eIF4E signaling based on studies in eIF4E S209A -knock-in mutant cells and animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little work has been done to understand how viral infections and sensory neurons interact to promote or suppress the immune response. However, the existing literature on sensory innervation of the airway and lung with bacterial pathogens suggests that sensory afferents can have detrimental and beneficial effects depending on the context (Chiu et al, 2012;Chavan et al, 2018;Ruhl et al, 2020). We have interpreted our interactome findings under the assumption that neurogenic responses may worsen the disease state in COVID-19, potentially leading to ARDS Table 3 Differentially expressed genes in BALF of COVID-19 patients that are known to be regulated by MNK -eIF4E signaling based on studies in eIF4E S209A -knock-in mutant cells and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Many, if not most, of these factors excite nociceptors, causing them to release specialized neuropeptides like calcitonin gene-related peptide (CGRP) and substance P (SP) that cause vasodilation and plasma extravasation (Sann and Pierau, 1998) and also have direct effects on lung immune cells (Baral et al, 2018;Wallrapp et al, 2019). Research on pulmonary infection and cough has highlighted the critical role that nociceptors play in promotion of airway diseases (Hadley et al, 2014;Narula et al, 2014;Talbot et al, 2015;Bonvini et al, 2016;Baral et al, 2018;Garceau and Chauret, 2019;Ruhl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SL-1 have no effect on virulence of Mtb in the mouse and guinea pig model (Rousseau et al, 2003b;Chesne-Seck et al, 2008). Recently, a study found a crucial role of SL-1 in the transmission process of Mtb by stimulating cough in guinea pigs (Ruhl et al, 2020). Indeed, SL-1 activates nociceptive neurons which triggers the coughing reflex and consistently, guinea pigs infected with a SL-1-deficient Mtb strain do not cough and do not transmit bacteria to uninfected guinea pigs (Ruhl et al, 2020).…”
Section: Tdm Dat/pat Sl-1mentioning
confidence: 99%
“… 16 Another example is in tuberculosis where the Mycobacterium tuberculosis produces sulfolipid-1 that acts on transient receptor potential vanilloid type 1 (TRPV1)-positive neurons to evoke cough. 73 On the other end of this spectrum, nociceptors can also play a key role in reducing bacterial pathogenesis, such as in the case of Salmonella enterica where calcitonin gene-related peptide released from TRPV1-positive neurons protects against infection after the detection of the pathogen by nociceptor nerve endings in the gut. 42 These studies demonstrate the intricacies of how bacteria can interact with nociceptors to promote pain, influence infection severity, or play a key role in promoting the spread of disease.…”
Section: Introductionmentioning
confidence: 99%